Photocurable O-carboxymethyl chitosan derivatives for biomedical applications: Synthesis, in vitro biocompatibility, and their wound healing effects - Na, Ha-Na; Park, Shin-Hye; Kim, Kwang-Il; Kim, Mi Kyung; Son, Tae-Il (Macromolecular research, 2012)
In this work, photocurable water-soluble chitosan derivatives were prepared for biomedical applications by modifying water-soluble O -carboxymethyl chitosan ( O -CMC) derivatives with furfuryl glycidyl ether ( O -CMC/FGE). Successful derivatization of chitosan to the final product ( O -CMC/FGE) was verified by UV and 1 H NMR spectral analysis. The degree of photo-crosslinking was measured by a flow distance experiment after exposure to visible light for a certain period of time. The degree of crosslinking increased linearly in proportion to exposure time. The in vitro cell viability test revealed a lack of cytotoxicity of O -CMC/FGE against mouse 3T3 fibroblasts. However, poor cell attachment was observed for the cells seeded onto the photocured O -CMC/FGE; this is likely due to the anionic nature of this material. O -CMC/FGE displayed wound healing effects in an in vivo animal experiment using a burn wound model. Due to its good biocompatibility, wound healing effect, and mild cross-linking condition, together with an inhibitory effect on cell attachment, O -CMC/FGE would be a promising candidate as an anti-adhesion material for biomedical applications.